2017
DOI: 10.1021/acsami.7b13402
|View full text |Cite
|
Sign up to set email alerts
|

AFM Nanoindentation To Quantify Mechanical Properties of Nano- and Micron-Sized Crystals of a Metal–Organic Framework Material

Abstract: The mechanical properties of individual nanocrystals and small micron-sized single crystals of metal-organic frameworks (MOFs), hitherto, cannot be measured directly by employing the conventional instrumented nanoindentation approach. Here we propose the application of atomic force microscopy (AFM)-based nanoindentation technique, equipped with a calibrated diamond cube-corner indenter tip to quantify the Young's modulus, hardness, adhesion energy, and interfacial and fracture strengths of a zeolitic imidazola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 70 publications
2
71
1
Order By: Relevance
“…Although it has been reported that the crystal size of ZIF-8 may influence the water intrusion pressure, 33 it remains to be established whether ZIF-8's framework flexibility and relaxation behavior are also size dependent subject to liquid intrusion. It is envisaged that our findings not only will open up the field of rate-dependent MOF mechanics, [39][40][41] but also lead to new MOF-based nanofluidic innovations. 22,42 For example, highrate liquid intrusion performance is critical for applications like impact mitigators and shock absorbers afforded by nanoporous materials.…”
Section: Discussionmentioning
confidence: 87%
“…Although it has been reported that the crystal size of ZIF-8 may influence the water intrusion pressure, 33 it remains to be established whether ZIF-8's framework flexibility and relaxation behavior are also size dependent subject to liquid intrusion. It is envisaged that our findings not only will open up the field of rate-dependent MOF mechanics, [39][40][41] but also lead to new MOF-based nanofluidic innovations. 22,42 For example, highrate liquid intrusion performance is critical for applications like impact mitigators and shock absorbers afforded by nanoporous materials.…”
Section: Discussionmentioning
confidence: 87%
“…The densities of FPOP-100 (1 = 1440.03 AE 46.29 kg m À3 ) and FPOP-101 (1 = 1451.61 AE 20.67 kg m À3 )a re higher than that of ZIF-8 ( Figure 6), which has nearly the same E but higher H (H{110} of ZIF-8:5 31 AE 28 MPa). [26,33] This higher hardnesso f ZIF-8 indicatesi ts ability to withstand higher load when the projected area of residual impression stays the same for both ZIF-8 and FPOPs. In other words, under the same indentation load, FPOPs suffer more permanent deformation,w hich could be plastic deformation of the network until eventual bond breakage.…”
Section: Resultsmentioning
confidence: 92%
“…Densities ρ of FPOP s were measured by using a Mettler Toledo instrument on the basis of the Archimedes principle. The densities of FPOP‐100 ( ρ =1440.03±46.29 kg m −3 ) and FPOP‐101 ( ρ =1451.61±20.67 kg m −3 ) are higher than that of ZIF‐8 (Figure ), which has nearly the same E but higher H ( H {110} of ZIF‐8: 531±28 MPa) . This higher hardness of ZIF‐8 indicates its ability to withstand higher load when the projected area of residual impression stays the same for both ZIF‐8 and FPOPs.…”
Section: Resultsmentioning
confidence: 99%
“…Intact pollen particles were chosen for extracting the Young's modulus of the exine layer and broken pollen particles, which exposed the inner layer, were chosen to determine the Young's modulus of the intine layer. In order to avoid the substrate effect, we followed the 10% depth rule where the indentation depth should be less than 1/10th of the layer thickness 38 . The average thickness of the exine layer was~0.6 μm for defatted pollen particles and 0 h KOH-treated pollen specimens, and became thinner with increasing KOH treatment time (~0.5 μm).…”
Section: Methodsmentioning
confidence: 99%